Further Advances in Pragmatics and Philosophy: Part 2 Theories and Applications - Capone, Alessandro; Carapezza, Marco; Lo Piparo, Franco (Perspectives in Pragmatics, Philosophy & Psychology, 2019)
The two sections of this volume present theoretical developments and practical applicative papers respectively. Theoretical papers cover topics such as intercultural pragmatics, evolutionism, argumentation theory, pragmatics and law, the semantics/pragmatics debate, slurs, and more. The applied papers focus on topics such as pragmatic disorders, mapping places of origin, stance-taking, societal pragmatics, and cultural linguistics. This is the second volume of invited papers that were presented at the inaugural Pragmasofia conference in Palermo in 2016, and like its predecessor presents papers by well-known philosophers, linguists, and a semiotician. The papers present a wide variety of perspectives independent from any one school of thought. .